Determination of Young's elastic modulus of plywood of Eucalyptus nitens (Deane & Maiden) - Muñoz-Acosta, Freddy (2012)
It was determined the Young`s elastic modulus (EMO) by three methods in a five-layer plywood from Eucalyptus nitens wood. The control method had the lowest variability (22,45 %). The lower standard error respect to control method, corresponds to method 2 with a coefficient of 0,566. While, the higher variability correspond to method 3 (29,91%). However, the ANOVA indicates not significant difference between the means of each method. The average of Young`s elastic modulus obtained of 10,18 GPa in axial direction, indicates that the elastic behavior of plywood is similar to E. nitens solid wood (9,6 GPa). In addition, EMO obtained indicates that the plywood meets the requirements of brazilian standards NBR 9531 and NBR 9523 and european EN 310-1993, allowing its use in interior light construction, as concrete mold, furniture and general uses, although, according to APA standard not classified for heavy construction, marine and industrial use.